Generation of a white-albino phenotype from cobalt blue and yellow-albino rainbow trout (Oncorhynchus mykiss): Inheritance pattern and chromatophores analysis. - Ricardo Shohei Hattori; Tulio Teruo Yoshinaga; Arno Juliano Butzge; Shoko Hattori-Ihara; Ricardo Yasuichi Tsukamoto; Neuza Sumico Takahashi; Yara Aiko Tabata (PLoS ONE)
Albinism is the most common color variation described in fish and is characterized by a white or yellow phenotype according to the species. In rainbow trout Oncorhynchus mykiss, aside from yellow-albino phenotypes, cobalt blue variants with autosomal, recessive inheritance have also been reported. In this study, we investigated the inheritance pattern and chromatophores distribution/abundance of cobalt blue trouts obtained from a local fish farm. Based on crosses with wild-type and dominant yellow-albino lines, we could infer that cobalt blue are dominant over wild-type and co-dominant in relation to yellow-albino phenotype, resulting in a fourth phenotype: the white-albino. Analysis of chromatophores revealed that cobalt blue trouts present melanophores, as the wild-type, and a reduced number of xanthophores. As regards to the white-albino phenotype, they were not only devoid of melanophores but also presented a reduced number of xanthophores. Cobalt blue and white-albino trouts also presented reduced body weight and a smaller pituitary gland compared to wild-type and yellow-albino phenotypes. The transcription levels of tshb and trh were up regulated in cobalt blue compared to wild type, suggesting the involvement of thyroid hormone in the expression of blue color. These phenotypes represent useful models for research on body pigmentation in salmonids and on the mechanisms behind endocrine control of color patterning.